Effects of Polyester Microplastic Fiber Contamination on Amphibian–Trematode Interactions. (4th May 2021) - Buss, Nicholas; Sander, Brianna; Hua, Jessica
Abstract: Microplastic contamination poses a global threat to aquatic organisms, yet we know little as to how microplastics may indirectly affect organismal health via their influence on species–species interactions (e.g., host–parasite interactions). This is problematic because microplastic‐mediated alterations to host–parasite dynamics could negatively impact individual‐ population‐level health of hosts. Using a larval amphibian (host) and free‐living trematode (parasite) model, we asked whether 1) polyester microplastic fibers influence parasite survival; 2) whether polyester microplastic fiber ingestion by amphibians alters amphibian susceptibility to infection; and 3) whether simultaneous exposure of amphibians and trematodes to polyester microplastic fibers influences infection outcomes. Polyester microplastic fibers did not alter trematode survival, nor did their ingestion by amphibians increase amphibian susceptibility to infection. However, when amphibians and trematodes were exposed simultaneously to the fibers, the infection success of the parasite was reduced. Lastly, we conducted a field survey for microfiber contamination across multiple ponds and found microfibers across each of the sampled ponds. Overall, our results contribute to the limited knowledge surrounding the ecological consequences of microplastic contamination. Environ Toxicol Chem 2022;41:869–879. © 2021 SETAC Abstract : Shown are: 1) the effect of microfiber contamination on free‐living trematode parasite survival; 2) the impact of microfiber ingestion on tadpole susceptibility to parasitic infection by trematode parasites; and 3) the impact of simultaneous microfiber exposure on the host–parasite interactions of amphibians and trematodes. MP = microplastic.